Sex Differences in the Pro-Angiogenic Response of Human Endothelial Cells: Focus on PFKFB3 and FAK Activation - Boscaro, Carlotta; Trenti, Annalisa; Baggio, Chiara; Scapin, Chiara; Trevisi, Lucia; Cignarella, Andrea; Bolego, Chiara (Frontiers in Pharmacology, 2020)
Female hormones and sex-specific factors are established determinants of endothelial function, yet their relative contribution to human endothelium phenotypes has not been defined. Using human umbilical vein endothelial cells (HUVECs) genotyped by donor’s sex, we investigated the influence of sex and estrogenic agents on the main steps of the angiogenic process and on key proteins governing HUVEC metabolism and migratory properties. HUVECs from female donors (fHUVECs) showed increased viability (p<0.01) and growth rate (p<0.01) compared with those from males (mHUVECs). Despite higher levels of G-protein coupled estrogen receptor (GPER) in fHUVECs (p<0.001), treatment with 17β-estradiol (E2) and the selective GPER agonist G1 (both 1-100 nM) did not affect HUVEC viability. Migration and tubularization in vitro under physiological conditions were higher in fHUVECs than in mHUVECs (p<0.05). E2 treatment (1-100 nM) upregulated the glycolytic activator PFKFB3 with higher potency in fHUVECs than in mHUVECs, despite comparable baseline levels. Moreover, Y576/577 phosphorylation of focal adhesion kinase (FAK) was markedly enhanced in fHUVECs (p<0.001), despite comparable Src activation levels. While the PI3K inhibitor LY294002 (25 µM) inhibited HUVEC migration (p<0.05), Akt phosphorylation levels in fHUVECs and mHUVECs were comparable. Finally, digitoxin treatment, which inhibits Y576/577 FAK phosphorylation, abolished sexual dimorphism in HUVEC migration. These findings unravel complementary modulation of HUVEC functional phenotypes and signaling molecules involved in angiogenesis by hormone microenvironment and sex-specific factors, and highlight the need for sex-oriented pharmacological targeting of endothelial function.